In Silico design of AVP (4-5) peptide and synthesis, characterization and in vitro activity of chitosan nanoparticles - Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin; Cakir-Koc, Rabia; Zorlu, Tolga; Bicak, Bilge; Kokcu, Yagmur; Ozel, Aysen E.; Akyuz, Sevim (SPRINGER INT PUBL AG, 2020)
Background Arginine-vasopressin (AVP) is a neuropeptide and provides learning and memory modulation. The AVP (4-5) dipeptide corresponds to the N-terminal fragment of the major vasopressin metabolite AVP (4-9), has a neuroprotective effect and used in the treatment of Alzheimer's and Parkinson's disease. Methods The main objective of the present study is to evaluate the molecular mechanism of AVP (4-5) dipeptide and to develop and synthesize chitosan nanoparticle formulation using modified version of ionic gelation method, to increase drug effectiveness. For peptide loaded chitosan nanoparticles, the synthesized experiment medium was simulated for the first time by molecular dynamics method and used to determine the stability of the peptide, and the binding mechanism to protein (HSP70) was also investigated by molecular docking calculations. A potential pharmacologically features of the peptide was also characterized by ADME (Absorption, Distribution, Metabolism and Excretion) analysis. The characterization, in vitro release study, encapsulation efficiency and loading capacity of the peptide loaded chitosan nanoparticles (CS NPs) were performed by Dynamic Light Scattering (DLS), UV-vis absorption (UV), Scanning Electron Microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy techniques. Additionally, in vitro cytotoxicity of the peptide on human neuroblastoma cells (SH-SY5Y) was examined with XTT assay and the statistical analysis was evaluated. Results The results showed that; hydrodynamic size, zeta potential and polydispersity index (PdI) of the peptide-loaded CS NPs were 167.6 nm, +13.2 mV, and 0.211, respectively. In vitro release study of the peptide-loaded CS NPs showed that 17.23% of the AVP (4-5)-NH2 peptide was released in the first day, while 61.13% of AVP (4-5)-NH2 peptide was released in the end of the 10th day. The encapsulation efficiency and loading capacity were 99% and 10%, respectively. According to the obtained results from XTT assay, toxicity on SHSY-5Y cells in the concentration from 0.01 mu g/mu L to 30 mu g/mu L were evaluated and no toxicity was observed. Also, neuroprotective effect was showed against H2O2 treatment. Conclusion The experimental medium of peptide-loaded chitosan nanoparticles was created for the first time with in silico system and the stability of the peptide in this medium was carried out by molecular dynamics studies. The binding sites of the peptide with the HSP70 protein were determined by molecular docking analysis. The size and morphology of the prepared NPs capable of crossing the blood-brain barrier (BBB) were monitored using DLS and SEM analyses, and the encapsulation efficiency and loading capacity were successfully performed with UV Analysis. In vitro release studies and in vitro cytotoxicity analysis on SHSY-5Y cell lines of the peptide were conducted for the first time.
Keywords: AVP (4-5); Hsp70; Drug delivery; Nanoparticle; Chitosan; Parkinson; MD; ARGININE-VASOPRESSIN; ACCURATE DOCKING; CELL VIABILITY; DRUG-DELIVERY; PROTEIN; GLIDE; PERMEABILITY; CHAPERONES; MODEL; Pharmacology & Pharmacy